Geosynthetics protecting the environment proceedings of the 1st IGS UK Chapter National Geosynthetics Symposium held at the Nottingham Trent University, on 17 June 2003 ; editors, N. Dixon ... [et al.]. - Dixon, N., Dr (Thomas Telford, 2003)
This publication presents recent advances in the design, maufacture, development and use of geosynthetics in environmental applications. the publication covered a wide range of issues relevant to those working in areas providing environmental protection through engineering measures (e.g those workin in waste management, contaminatied land and urban drainage).